Impact of intracellular ion channels on cancer development and progression - Roberta Peruzzo; Lucia Biasutto; Ildikò Szabó; Luigi Leanza (2016)
Cancer research is nowadays focused on the identification of possible new targets in order to try to develop new drugs for curing untreatable tumors. Ion channels have emerged as "oncogenic" proteins, since they have an aberrant expression in cancers compared to normal tissues and contribute to several hallmarks of cancer, such as metabolic re-programming, limitless proliferative potential, apoptosis-resistance, stimulation of neo-angiogenesis as well as cell migration and invasiveness. In recent years, not only the plasma membrane but also intracellular channels and transporters have arisen as oncological targets and were proposed to be associated with tumorigenesis. Therefore, the research is currently focusing on understanding the possible role of intracellular ion channels in cancer development and progression on one hand and, on the other, on developing new possible drugs able to modulate the expression and/or activity of these channels. In a few cases, the efficacy of channel-targeting drugs in reducing tumors has already been demonstrated in vivo in preclinical mouse models.